2021
DOI: 10.3390/pathogens10010083
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Diagnosis of Small Ruminant Lentivirus Infection Is Needed for Selection of Resistant Sheep through TMEM154 E35K Genotyping

Abstract: Small ruminant lentiviruses (SRLV) cause an incurable multiorganic disease widely spread in sheep and goats that disturbs animal welfare and production. In the absence of a vaccine, control measures have been traditionally based on early diagnosis and breeding with virus-inactivated colostrum with segregation of seropositive animals. However, antigenic heterogeneity, poor antibody production due to low viral load, and single strain design of most available ELISA, pose a threat to SRLV diagnosis. Genome-wide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
2
16
0
4
Order By: Relevance
“…Genetic variations that generate amino acid substitutions gave rise to 15 different and unambiguous haplotypes that included 100% of the observed ones as a result of the presence of only one polymorphic site in heterozygosity. Specifically, we identified six already known (1, 2, 3, 4, 6, 16) and nine novel haplotypes (17)(18)(19)(20)(21)(22)(23)(24)(25) reported in Table S1.…”
Section: Tmem154 Tlr9 Myd88 and Ccr5 Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations that generate amino acid substitutions gave rise to 15 different and unambiguous haplotypes that included 100% of the observed ones as a result of the presence of only one polymorphic site in heterozygosity. Specifically, we identified six already known (1, 2, 3, 4, 6, 16) and nine novel haplotypes (17)(18)(19)(20)(21)(22)(23)(24)(25) reported in Table S1.…”
Section: Tmem154 Tlr9 Myd88 and Ccr5 Genotypingmentioning
confidence: 99%
“…TMEM154 gene encodes for a precursor protein of 191 amino acids that mature in a protein of 161 amino acids, but its biological function is still unknown. Some studies showed that the amino acid substitution glutamate tolysine (E/K) in position 35 (rs408593969) can modulate the predisposition to the infection, in particular the KK genotype is associated to a decrease in susceptibility together with low serological levels [ 9 , 15 , 16 , 17 , 18 , 19 ]. However, other authors reported that the KK genotype is not fully protective depending on several possible factors as viral dose, route of infection, type and number of SRLVs strains involved, comorbidities, other environmental and genetic factors [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to identify host factors associated with resistance to SRLV infections have been made, and some loci were identified [11][12][13][14][15]. In particular TMEM154 gene (transmembrane protein 154), TMEM38A (transmembrane protein 38A), CCR5 (chemokine(C-C motif) receptor type 5), MHC (major histocompatibility complex), ZNF389 (zinc-finger protein 389), TLRs (toll-like receptors), APOBEC3 (apolipoprotein B editing complex 3), TRIM5 (tripartite motif protein 5 alpha), Tetherin/BST-2 (bone marrow stromal cell antigen 2) and other cytokines (interleukin 2 (IL2), interleukin 2 receptor (IL2R), tumor necrosis factor alfa (TNF-α), interleukin 4 (IL4), interleukin 8 (IL8), interleukin 6 (IL6), interleukin 16 (IL-16), interferon gamma (IFN-γ), transforming growth factor beta (TGF-β1), monocyte chemoattractant protein-1 (MCP-1), granulocyte-macrophage colony-stimulating factor (GM-CSF)) and chemokine ligands (C-C motif ligand 2 (CCL2), C-C motif ligand 5 (CCL5), C-C motif ligand 20 (CCL20)) seem to have an important role in the SRLV infection susceptibility/resistance [12,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. However, additional studies are still necessary to learn more about genes involved in SRLV immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, except for the impediments arising from virus nature and the immunopathological mechanisms, a critical endeavor for the enhancement of serological diagnosis performance is to enrich the antigenic design of ELISA and improve its negative predictive value. The use of whole virus, incorporation of multiple antigens and synthetic peptide combinations, and genotype-specific immunodominant epitopes have been proposed for the extension of the antigenic spectrum and the amplification of the detection capacity of the assay [54,[56][57][58]60,62,63].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…A “gold standard” test with high values of sensitivity, specificity and accuracy, blindly used in every case does not seem readily feasible when considering the special characteristics of SRLVs (i.e., high genetic variability, mechanisms of virus replication, and animal humoral immune response). Nonetheless, the scientific community has addressed these limitations, proposing targeted combinations of diagnostic tools, which are constantly evaluated to reduce the possibility of both newly or persistently infected animals to evade diagnosis [ 27 , 39 , 62 , 63 , 70 , 82 , 86 , 101 , 102 ]. Although combination of diagnostics increases cost, time, and the effort required, it seems to be inevitable for the early and safe diagnosis in young animals which are likely infected but seronegative.…”
Section: Current and Future Perspectives In Diagnosis Of Srlv Infectionsmentioning
confidence: 99%